Prostate cancer cells of increasing metastatic potential exhibit diverse contractile forces, cell stiffness, and motility in a microenvironment stiffness-dependent manner - Molter, Clayton W.; Muszynski, Eliana F.; Tao, Yuanyuan; Trivedi, Tanisha; Clouvel, Anna; Ehrlicher, Allen J. (Frontiers in Cell and Developmental Biology, 2022)
During metastasis, all cancer types must migrate through crowded multicellular environments. Simultaneously, cancers appear to change their biophysical properties. Indeed, cell softening, and increased contractility are emerging as seemingly ubiquitous biomarkers of metastatic progression which may facilitate metastasis. Cell stiffness and contractility are also influenced by the microenvironment; stiffer matrices resembling the tumor microenvironment causes metastatic cells to contract more strongly, further promoting contractile tumorigenic phenotypes. Prostate Cancer (PCa), however, appears to deviate from these common cancer biophysics trends; aggressive metastatic PCa cells appear stiffer, rather than softer, to their lowly metastatic PCa counterparts. Although metastatic PCa cells have been reported to be more contractile than healthy cells, how cell contractility changes with increasing PCa metastatic potential has remained unknown. Here we characterize the biophysical changes of PCa cells of various metastatic potential as a function of microenvironment stiffness. Using a panel of progressively increasing metastatic potential cell lines (22RV1, LNCaP, DU145, PC3), we quantified their contractility using Traction Force Microscopy (TFM), measured their cortical stiffness using Optical Twisting Magnetic Cytometry (OMTC), and their motility using time-lapse microscopy. We found that PCa contractility, cell stiffness, and motility do not universally scale with metastatic potential. Rather PCa of various metastatic efficiencies exhibit unique biophysical responses that are differentially influenced by substrate stiffness. Despite this biophysical diversity, this work concludes that the mechanical microenvironment is a key determinant in the biophysical response of PCa with variable metastatic potentials. The mechanics-oriented focus and methodology of the study is unique and complementary to conventional biochemical and genetic strategies typically used to understand this disease, and thus may usher in new perspectives and approaches.